Les usages militants d’Internet - Éric George (Communication)
We propose to question the characteristics of the possible formation of a « transnational public space » through the mobilization of the Internet and on the part of the « alterworldist movement. » We will approach this question by studying the development of the uses within the international organization NTTAC, born in France in 1998 and five years later, present in some 50 countries. This analysis allows us to foreground many of the potential contributions of the information network in terms of international communication, but also sheds light on the risks of not taking the considerable inequalities which exist on the global scale into account. Beyond the technical and social aspects linked to the internet, the possible formation of a « transnational public space » will also depend on the relationships which will be built between political authorities and the components of the « alterworldist movement. »